Is theory development essential for the social work dissertation?. Issue 2 (17th February 2018) - Akesson, Bree; Braganza, Morgan; Root, Jennifer
Abstract: Grounded theory methodology (GTM) is a popular methodology used in social work dissertation research. GTM entails the development of theory 'grounded in' and generated from data systematically gathered and analyzed through qualitative methods. But little is known of its theory development and relationship to social work education at the doctoral level. In this article, we reflect on contemporary usage of GTM with respect to the state of theory development in social work education by reviewing a sample of Canadian social work doctoral dissertations that utilize GTM, identifying if and how theory was developed. Our analysis draws from a broader review of GTM research published as social work doctoral dissertations in Canada using the Qualitative Research Quality Checklist (QRQC). The findings indicate that almost half of the dissertations in the sample did not contribute to theory development, and for many, theory development was not the intention. This raises a question about whether theory development when utilizing GTM is essential in social work dissertation research, and perhaps, whether the focus should be on exploring a social work issue rather than generating theory. The paper concludes with considerations for social work educators in regards to research methodology, epistemology, and theory.